Pengembangan Aplikasi Supply Chain Management Berbasis Web untuk Optimalisasi Manajemen Persediaan di Toko Agen Sinar Jaya - Vincentius Danang Aryadutha; Nugroho Budhisantosa (SM Institute, 2025)
This research aims to develop a web-based Supply Chain Management (SCM) application to optimize inventory management at Sinar Jaya Agent Shop. The main problem faced is the lack of efficiency in stock management, which often leads to a mismatch between available stock and market needs. By utilizing web-based technology, this application is able to provide real-time stock updates, facilitate inventory monitoring, and increase accuracy in the decision-making process related to inventory management. The research methods used include needs analysis, system design, implementation, and application testing. The results showed that the developed SCM application succeeded in improving store operational efficiency, reducing the risk of stock-outs, and speeding up the restocking process. In addition, this system can also be integrated with sales and purchase reports, which allows store owners to conduct more in-depth data analysis.